2020
DOI: 10.1002/jcp.29914
|View full text |Cite
|
Sign up to set email alerts
|

Ptk2b deletion improves mice folliculogenesis and fecundity via inhibiting follicle loss mediated by Erk pathway

Abstract: Ptk2b has been found playing critical roles in oocyte maturation and subsequent fertilization in vitro. But what is the exact in vivo function in reproduction still elusive. Here, by constructing Ptk2b mutant mice, we found Ptk2b was not essential for mice fertility, unexpectedly, contrary to previously reported in vitro findings, we found Ptk2b ablation significantly improved female fecundity. Follicle counting indicated that the number of primordial follicles and growing follicles in matured mice was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The physiological role of the FOXO3a in the primordial follicle is to prevent oocytes from premature activation. However, when Bax and Ptk2b were knocked out, the reserve of primordial follicles in the ovary increased and the fertility of mice was prolonged 35,36 . We also found that when Sp1 was knocked out in GCs, the depletion of primordial follicles was reduced.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The physiological role of the FOXO3a in the primordial follicle is to prevent oocytes from premature activation. However, when Bax and Ptk2b were knocked out, the reserve of primordial follicles in the ovary increased and the fertility of mice was prolonged 35,36 . We also found that when Sp1 was knocked out in GCs, the depletion of primordial follicles was reduced.…”
Section: Discussionmentioning
confidence: 64%
“…However, when Bax and Ptk2b were knocked out, the reserve of primordial follicles in the ovary increased and the fertility of mice was prolonged. 35,36 We also found that when Sp1 was knocked out in GCs, the depletion of primordial follicles was reduced. However, more growing follicles in the aging GC-Sp1 −/− mice ovary based on this study indicated that the surviving primordial follicles developed normally and that the fertility was prolonged.…”
Section: Discussionmentioning
confidence: 66%
“…Protein-tyrosine kinase 2 beta ( PTK2B ) is a member of the focal adhesion kinase family and plays a key role in oocyte maturation and in vitro fertilization [ 41 , 42 ]. Sharma et al found that PTK2B is expressed in zebrafish oocytes and affects zebrafish reproduction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al found that PTK2B can mediate the process of early embryonic development in mice [ 42 ]. It was reported that PTK2B regulates female fertility by regulating the process of ovarian and follicle formation, and when it is inhibited, oocyte maturation and ovarian development are affected [ 41 ]. In addition, PTK2B was found to be involved in the process of human sperm capacitation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, other PFR-improving strategies beyond inhibition of mTOR activators, such as activating the SIRT1/FOXO1 signaling through hADSC-secreted HGF and bFGF (19) or up-regulating erk phosphorylation through Ptk2b knockout (20), could not specifically target ovaries as well and carry the risk of tumorigenesis (21,22).…”
Section: Introductionmentioning
confidence: 99%